Dual Use of Cover Crops for Forage Production and Soil Health in Dryland Crop Production - A. K. Obour; J. D. Holman; L. M. Simon; S. K. Johnson (Kansas Agricultural Experiment Station Research Reports, 2020)
Integrating a cover crop (CC) into dryland crop production in the semiarid central Great Plains (CGP) can provide several ecosystem benefits. However, CC adoption is slow and not widely popular in the CGP because CCs utilize water that otherwise would be available for the subsequent cash crop. Grazing or haying CCs can provide economic benefits to offset revenue loss associated with decreased crop yields when CCs are grown ahead of a cash crop. Objectives of the current research were to 1) determine forage production of CC mixtures, and 2) evaluate the impacts of removing CCs for forage on subsequent crop yields and soil health. Cover crop treatments evaluated were a mixture of oat and triticale that were either grazed, hayed or left standing compared to chem-fallow. The study was conducted from 2015 to 2019 in a wheat-sorghum-fallow cropping system with all crop phases present in each block and year of the study. Results showed forage mass varied from year-to-year, ranging from 3145 lb/a in 2015 to 1655 lb/a in 2019, and was highly dependent on growing season precipitation and temperature. Forage crude protein, digestibility, and mineral concentrations were greatest in years when CCs were sampled earlier in maturity. Average CC residue left post-grazing was 79% of forage mass available pre-grazing, and ranged from 60% in 2016 (no regrowth) to 123% in 2019 (more regrowth). Growing CCs ahead of wheat reduced winter wheat yield in 2 out of the 4 years compared to chem-fallow. Across years, winter wheat yield with chem-fallow was 51.9 bu/a compared to an average of 41.8 bu/a for the CC treatments. Cover crop treatments had no effect on grain sorghum yield. Sorghum grain yield ranged from 70.7 bu/a with CC hayed to 77.0 bu/a for the CC grazing treatment. Winter wheat or sorghum yields with haying or grazing a CC were similar to yields when CCs were left standing. Grazing CCs increased bulk density near the soil surface in 1 of the 4 years when bulk density was measured. Compared to fallow, growing a CC increased soil organic carbon (SOC) concentration measured within the top 2- to 6-inch soil depth, but not near the soil surface (0 to 2 inches).
Keywords: cover crops; dryland; forage; grazing; soil organic matter